Phenylbutyrate Treatment in a Boy With MCT8 Deficiency: Improvement of Thyroid Function Tests and Possible Hepatotoxicity. - Schreiner, Felix; Vollbach, Heike; Sonntag, Niklas; Schempp, Vera; Gohlke, Bettina; Friese, Johannes; Wölfle, Joachim; Braun, Doreen; Schweizer, Ulrich (Journal of Clinical Endocrinology and Metabolism, 2025)
CONTEXT: Monocarboxylate transporter 8 (MCT8) deficiency is a rare X-chromosomal inherited disease leading to severe cognitive impairment, muscular hypotonia, and symptoms of peripheral thyrotoxicosis. Experimental approaches aiming to functionally rescue mutant MCT8 activity by the chemical chaperone phenylbutyrate (PB) demonstrated promising effects in vitro for several MCT8 missense mutations. OBJECTIVE: The objective was to evaluate biochemical and clinical effects of PB in doses equivalent to those approved for the treatment of urea cycle disorders in a boy with MCT8 deficiency due to a novel MCT8 missense mutation c.703G>T (p.V235L). RESULTS: During a treatment period of 13 months, PB led to a significant decrease of elevated thyrotropin and triiodothyronine (T3) serum concentrations, while free thyroxine (fT4) increased. The weight z-score of the toddler remained remarkably stable during the treatment period. Neurodevelopmental assessments (BSID-III) revealed a slight increase of gross motor skills from developmental age 4 to 6 months. However, increasing liver enzyme serum activities and accumulation of phenylacetate in urine led to treatment interruptions and dose alterations. In vitro analyses in MDCK1 cells confirmed the pathogenicity of MCT8 p.V235L. However, while PB increased expression of the mutant protein, it did not rescue T3 transport, suggesting a PB effect on thyroid function tests independent of restoring MCT8 activity. CONCLUSION: In a clinical attempt of PB treatment in MCT8 deficiency we observed a significant improvement of thyroid hormone function tests, tendencies toward body weight stabilization and slight neurodevelopmental improvement. Hepatotoxicity of PB may be a limiting factor in MCT8 deficiency and requires further investigation.
EVALuna2:586368